Climbing and Walking Robots Proceedings of the 8th International Conference on Climbing and Walking Robots and the Support Technologies for Mobile Machines (CLAWAR 2005) - Tokhi, M. O.; Virk, G. S.; Hossain, M. A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
The interest in climbing and walking robots (CLAWAR) has intensified in recent years, and novel solutions for complex and very diverse applications have been anticipated by means of significant progress in this area of robotics. The shift of robotics from manufacturing to services is clearly gaining pace as witnessed by the growth in activities in the CLAWAR area. Moreover, the amalgamation of original ideas and related innovations, search for new potential applications and the use of state of the art support technologies indicate that important steps are likely in the near future and the results could have a significant beneficial socio-economic impact. This book reports on state of the art latest research and development findings and results presented in the CLAWAR 2005 Conference. These are presented in 131 technical articles by authors from 27 countries worldwide. The book is structured into 21 sections, which include some of the traditional topics featured in previous CLAWAR conferences with a set of new topics such as bioengineering, flexible manipulators, personal assistance applications, non-destructive test applications, security and surveillance applications and space applications of robotics. The editors are grateful to colleagues within the committee structure of the CLAWAR 2005 for their help in the review process of the articles and their support throughout this project.
Plenary Papers -- Bio-Engineering and Biological Inspired Systems -- Climbing, Navigation and Path Planning -- Control of CLAWAR -- Design Methodology and Gait Generation -- Hopping and Legged Robots -- Humanoid Robots -- Locomotion -- Manipulation and Flexible Manipulators -- Modular, Reconfigurable Robots -- Modularity and System Architecture -- Powering, Actuation, Efficiency -- Sensing and Sensor Fusion -- Software and Computer-aided Environments -- System Analysis, Modelling and Simulation -- Industrial Applications -- Non-destructive Testing Applications -- Personal Assistance Applications -- Security and Surveillance Applications -- Space Applications -- Tele-operation, Social and Economic Aspects.
Keywords: Engineering; Artificial intelligence; Mechanical engineering; Control engineering; Robotics; Mechatronics; Automation; Engineering; Robotics and Automation; Control, Robotics, Mechatronics; Mechanical Engineering; Artificial Intelligence (incl. Robotics).; Electronic books